A study on genotoxicity of textile dyeing industry effluents from Rajshahi, Bangladesh, by the Allium cepa test. Issue 5 (28th May 2017) - Rahman, Md. Mahfuzur; Rahman, Md. Fazlur; Nasirujjaman, Khondokar
ABSTRACT: Textile dye effluents are believed to be toxic as they might exert various harmful effects on living organisms including genotoxicity. These effluents are the main source of direct and continuous input of pollutants into the aquatic ecosystems. In this study, dye effluents from a local silk dyeing industry were analysed for their genotoxic potential by the Allium cepa genotoxicity test. The A. cepa test is characterised as a genotoxicity test where the roots of A. cepa are grown in different concentrations of the test material. The macroscopic results clearly showed that the toxicity of the dye effluents prompted A. cepa root growth inhibition, and this effect increased with higher concentrations of the effluents. At the cellular level, no dividing cells were found at higher concentrations such as 60%, 80% and 100% of the effluents. However, at a lower concentration of 20%, dividing cells were identified, although the mitotic index was much lower than that of the control. Microscopic analysis showed that the dye effluents induced chromosomal aberrations at significant levels. Taken together, these results revealed that the textile dyeing industry effluents are toxic to eukaryotic cells and these dyes have genotoxic properties that can potentially lead to cancer development and adverse health conditions.